2016
DOI: 10.1021/acs.energyfuels.6b00285
|View full text |Cite
|
Sign up to set email alerts
|

Ash Fusion Characteristics of a High Aluminum Coal and Its Modification

Abstract: High aluminum coal (HAC, Al 2 O 3 in its ash content ranges 38−51%) is abundant and plays an important role in energy and chemical product in China. The ash fusion characteristics of HAC and its modification behaviors by coal blending or flux were investigated by ash fusion temperature (AFT) analyzer, X-ray fluorescence spectrometry, X-ray diffractometry combined with normalized reference intensity ratio method, and scanning electron microscopy. The AFT variation is manly dependent on mineral composition and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…3 Blending coal not only improves ash viscosity-temperature characteristics but also is more economical and efficient for raw material complementary and product structure optimization. 17 To make high-AFT coal meet the requirements of liquid slag discharge in the EFG, the coal preparation method is generally carried out by mixing the high-AFT coal with the low AFT coal. However, the regulation of AFTs was mainly focused on the control of HSAC, and little attention has been paid to other high melting point (MP) coals (e.g., HAC and HCC).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…3 Blending coal not only improves ash viscosity-temperature characteristics but also is more economical and efficient for raw material complementary and product structure optimization. 17 To make high-AFT coal meet the requirements of liquid slag discharge in the EFG, the coal preparation method is generally carried out by mixing the high-AFT coal with the low AFT coal. However, the regulation of AFTs was mainly focused on the control of HSAC, and little attention has been paid to other high melting point (MP) coals (e.g., HAC and HCC).…”
mentioning
confidence: 99%
“…The FTs of HAC and HCC are usually high (HAC: >1600 C; HCC: >1400 C). It was found that even if the blending coal mass ratio reached 60%, the FTs of mixed ashes did not decrease to meet the requirement of the EFG; however, when CaO reached 20%, the FTs of mixed ashes have been decreased to <1380 C. 17 Therefore, it is necessary to improve the coal preparation principle. For example, coal-blending experiments of Pingsuo coal and Shenhua coal and Tianci coal and Xiaotun coal indicated that the variation in the contents of mullite and anorthite were the main reason leading to the AFTs change.…”
mentioning
confidence: 99%
See 3 more Smart Citations